Tripal, a community update after 10 years of supporting open source, standards-based genetic, genomic and breeding databases. Issue 6 (12th July 2021) - Staton, Margaret; Cannon, Ethalinda; Sanderson, Lacey-Anne; Wegrzyn, Jill; Anderson, Tavis; Buehler, Sean; Cobo-Simón, Irene; Faaberg, Kay; Grau, Emily; Guignon, Valentin; Gunoskey, Jessica; Inderski, Blake; et al.
Abstract: Online, open access databases for biological knowledge serve as central repositories for research communities to store, find and analyze integrated, multi-disciplinary datasets. With increasing volumes, complexity and the need to integrate genomic, transcriptomic, metabolomic, proteomic, phenomic and environmental data, community databases face tremendous challenges in ongoing maintenance, expansion and upgrades. A common infrastructure framework using community standards shared by many databases can reduce development burden, provide interoperability, ensure use of common standards and support long-term sustainability. Tripal is a mature, open source platform built to meet this need. With ongoing improvement since its first release in 2009, Tripal provides full functionality for searching, browsing, loading and curating numerous types of data and is a primary technology powering at least 31 publicly available databases spanning plants, animals and human data, primarily storing genomics, genetics and breeding data. Tripal software development is managed by a shared, inclusive governance structure including both project management and advisory teams. Here, we report on the most important and innovative aspects of Tripal after 11 years development, including integration of diverse types of biological data, successful collaborative projects across member databases, and support for implementing FAIR principles.